"There is no alternative" : why Margaret Thatcher matters - Berlinski, Claire (Basic Books, 2008)
Great Britain in the 1970s appeared to be in terminal decline--ungovernable, an economic wreck, and rapidly headed for global irrelevance. Three decades later, it is the richest and most influential country in Europe, and Margaret Thatcher is the reason. The preternaturally determined Thatcher rose from nothing, seized control of Britain's Conservative party, and took a sledgehammer to the nation's postwar socialist consensus. She proved that socialism could be reversed, inspiring a global free-market revolution. Simultaneously exploiting every politically useful aspect of her femininity and defying every conventional expectation of women in power, Thatcher crushed her enemies with a calculated ruthlessness that stunned the British public and without doubt caused immense collateral damage. Ultimately, however, author Berlinski agrees with Thatcher: There was no alternative. Berlinski explains what Thatcher did, why it matters, and how she got away with it in this vivid portrait of one of the towering figures of the twentieth century.--From publisher description.